The Implementation of Deep Learning Based Islamic Education in SMK Batik 1 Surakarta - Nisrina Atiqoh S Jutin; Muhammad Wildan Shohib (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The rapid advancement of digital technology has transformed educational practices, demanding learning approaches that are adaptive, meaningful, and relevant to 21st-century learners. This study investigates the implementation of deep learning based Islamic Education at SMK Batik 1 Surakarta, focusing on its impact, challenges, and supporting strategies. The research employed a qualitative with a phenomenological approved. Data were collected through classroom observations, in-depth interviews with teachers and students, and documentation, and were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the implementation of deep learning emphasizes three core principles: mindful, meaningful, and joyful learning. Teachers function as facilitators by applying active learning models such as Problem Based Learning (PBL) and Project Based Learning (PjBL) to enhance critical thinking, collaboration, and student engagement. The approach strengthens students’ religious character and learning motivation. However, its implementation faces several challenges, including limited digital infrastructure, restrictions on gadget use, and limited instructional time. To address these issues, teachers adopt adaptive strategies such as alternative learning media, peer tutoring, and the integration of Islamic values into routine school activities. Overall, the success of this approach depends on teacher creativity and collaborative support from the school community..